2022
DOI: 10.31234/osf.io/859x3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism-related language preferences of English-speaking autistic adults across the globe: A mixed methods investigation

Abstract: Over the past two decades, there have been increasing discussions around which terms should be used to talk about autism. Whilst these discussions have largely revolved around the suitability of identity-first language and person-first language, more recently this debate has broadened to encompass other autism-related terminology (e.g., “high-functioning”). To date, academic studies have not investigated the language preferences of autistic individuals outside of the UK or Australia, nor have they compared lev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Several studies have shown the preferences of the autistic community for the use of identity-first language, although language use within the community is still varied (Angulo-Jiménez & DeThorne, 2019;APA, 2020;Botha et al, 2023;Bottema-Beutel et al, 2021;Buijsman et al, 2023;Bury et al, 2023;Keating et al, 2023;Kenny et al, 2016;Taboas et al, 2023). In this regard, there are conflicting ideologies in how autism is conceptualized by the autistic community and scholars.…”
Section: Language Use and Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the preferences of the autistic community for the use of identity-first language, although language use within the community is still varied (Angulo-Jiménez & DeThorne, 2019;APA, 2020;Botha et al, 2023;Bottema-Beutel et al, 2021;Buijsman et al, 2023;Bury et al, 2023;Keating et al, 2023;Kenny et al, 2016;Taboas et al, 2023). In this regard, there are conflicting ideologies in how autism is conceptualized by the autistic community and scholars.…”
Section: Language Use and Autismmentioning
confidence: 99%
“…This debate also reflects conflicting ideologies between this medicalized view and an identity and community perspective. According to Keating et al (2023), some English-speaking autistic adults reject the use of Asperger's syndrome because it "damages the unity of the community, and instead generates a hierarchy based on 'socially-valued' differences between autism and Asperger's syndrome"(p. 424). In the participants' view, this clinical and linguistic distinction is a reflection of patronizing language, which according to Bottema-Beutel et al ( 2021) is considered potentially ableist language.…”
Section: Condition: Labels For Clinical Entities or A Social Group?mentioning
confidence: 99%
“…We have elected to use the term autistic children, but also recognize that the best approach is to ask each person how they want to be identified as identity can be influenced by autistic identity and experiences of stigma (Bury et al, 2022). Researchers have also asserted that there is no universally accepted way to discuss autism (Keating et al, 2022). 4.…”
Section: Notesmentioning
confidence: 99%
“…In line with journal use guidelines informed by autistic self-advocates and stakeholders in the autism community, we refer to ASD as autism throughout this manuscript except when we use the abbreviation to delineate our groups(1,2). Similarly, we have decided to use identity-first language as much as possible(3,4).…”
mentioning
confidence: 99%